Maternal health care professionals' experiences and views on the use of obstetric ultrasound in Rwanda: A cross-sectional study - Ingrid Mogren; Joseph Ntaganira; Jean Paul Semasaka Sengoma; Sophia Holmlund; Rhonda Small; Lan Pham Thi; Hussein Lesio Kidanto; Matilda Ngarina; Cecilia Bergström; Kristina Edvardsson (BMC, 2021)
Abstract Background This study, undertaken in Rwanda, aimed to investigate health professionals' experiences and views on the following topics: current clinical guidelines for ultrasound from second trimester at the clinic, regional and national levels, and adherence to clinical guidelines; medically indicated ultrasound examinations; non-medical use of ultrasound including ultrasounds on maternal request; commercialisation of ultrasound; the value of ultrasound in relation to other clinical examinations in pregnancy; and ultrasound and medicalisation of pregnancy. Methods A cross-sectional design was adopted. Health professionals providing antenatal care and delivery services to pregnant women in 108 health facilities were invited to complete a survey, which was developed based on the results of earlier qualitative studies undertaken as part of the CROss Country Ultrasound Study (CROCUS). Results Nine hundred and seven health professionals participated: obstetricians/gynecologists (3.2%,) other physicians (24.5%), midwives (29.7%) and nurses (42.7%). Few physicians reported the existence of clinical guidelines at clinic, regional or national levels in Rwanda, and guidelines were moderately adhered to. Three obstetric ultrasound examinations were considered medically indicated in an uncomplicated pregnancy. Most participants (73.0%) were positive about obstetric ultrasound examinations on maternal request. Commercialisation was not considered a problem, and the majority (88.5%) agreed that ultrasound had contributed to medicalisation of pregnancy. Conclusions Findings indicate that clinical guidelines for the use of obstetric ultrasound are limited in Rwanda. Non-medically indicated obstetric ultrasound was not considered a current problem at any level of the healthcare system. The positive attitude to obstetric ultrasound examinations on maternal request may contribute to further burden on a maternal health care system with limited resources. It is essential that limited obstetric ultrasound resources are allocated where they are most beneficial, and clearly stated medical indications would likely facilitate this.